Segmental Arterial Mediolysis: A Case of Mistaken Hemorrhagic Pancreatitis and Review of the Literature - Horsley-Silva, Jennifer L; Ngamruenphong, Saowanee; Frey, Gregory T; Paz-Fumagalli, Ricardo; Lewis, Michele D (JOP. Journal of the Pancreas, 2014)
Context Segmental arterial mediolysis is an uncommon, non-atherosclerotic, non-inflammatory arteriopathy that involves areas of dissecting aneurysms and strictures that are caused by outer media lysis of the arterial wall from areas of medial necrosis of uncertain pathogenesis. It has a predilection for splanchnic arteries and often presents as abdominal pain or hemorrhage in late middle-aged and elderly patients. Diagnosis can be established by computed tomography angiography, magnetic resonance angiography, or angiogram by visualizing typical abnormalities, in addition to excluding other vasculitides. Histological confirmation is the gold standard but is not easily accessible and, as such, is not frequently performed. Case report Here we present an updated review of the literature and a case of segmental arterial mediolysis that presented with spontaneous intra-abdominal bleeding near the pancreas that was originally misdiagnosed as hemorrhagic pancreatitis. Conclusion Diagnosis is important because immunosuppressants for vasculitis can worsen the arteriopathy. Segmental arterial mediolysis can be self-limiting without treatment or may require urgent surgical or endovascular therapy for bleeding and carries a 50% mortality rate. Therefore, it should be included in the differential of causes of abdominal pain as well as in cases of unexplained abdominal hemorrhage. Image: Vascular irregularity and pseudoaneurysm formation.